THE IMPLEMENTATION OF CLASSROOM-BASED ASSESSMENT IN AN INTERNATIONAL STANDARD JUNIOR HIGH SCHOOL IN YOGYAKARTA - Eko Windu Prasetya; Yanuarius Yanu Dharmawan (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2019)
This study attempts to answer the research question on the implementation of classroom-based assessment in an International standard Junior High school in Yogyakarta. Thus, this study is written to get complete understanding on the assessment process which is applied in International standard Junior High School. In order to interpret the data in this study, Creswell (2003) and Nunan (2009) suggest that the writer should conduct several steps. First, prepare the data; questionnaire and interviews transcription and arrange it based on its source. Second, draw the general idea from each data. Third analyze each data in detail trough coding process. Fourth, generate a description based on the coding result. Fifth, develop the description into a qualitative narrative report. Last, interpret in the report to answer the research question. In conclusion, the International Standard Junior High School in Jogjakarta has not applied the classroom-based assessment. This fact is mainly because of the condition in the real situation hasn’t permitted the implementation of classroom-based assessment. Teacher is International Standard of Junior High school is busy with the preparation for National Examination. Thus, they only focus to make the students familiar with the test format so that they can pass the National examination.